THE COMPARİSON OF ASSYST, KONSANCAD AND LECTRA SYSTEMS WHİCH ARE COMPUTER- SUPPORTED PATTERN PREPARATİON SYSTEMS USED İN READY-MADE CLOTHİNG SECTOR İN TURKEY - Mücella ÖZKAN (Fırat University, 2019)
It forms the aim of the research that the comparison of Assyst, Konsancad and Lectra systems which are Computer- supported pattern preparation systems used in ready-made clothing sector. In determination of the systems , it has been decided that among the available Systems, Assyst, Konsancad and Lectra Systems are suitable for the research, analysis of Systems has been completed in alphabetical order (Assyst, Konsancad , Lectra). While all Computer-supported pattern preparation systems used in ready- made clothing sector constitute the universe of the research prefered Systems Constitute the illustration of the exploration during the research. While researching, firstly information scanning about ready- made clothing sector in turkey and on the World has been completed. Scanning the sources for each system, literature information Systems has been gained. Advantages and disaduantages of each of three Systems has been tried to be fixed. In addition to that for each system not only the same model and cloth also the same breadth being fixed, an example laying plan, a lay was made at first concerning the direction of the cloth, then not concerning it. As a result of these lays, it has been fixed that how productive settlement each system made and their loss rate.